Estimulação elétrica pré-incisional na cicatrização em pele de rato - Borba, Graziela Maria Chacon [UNIFESP] (2009)
BACKGRAUND: In vitro studies have demonstrated that electrical current may affect the proliferation of fibroblast, and synthesis of collagen fibers. OBJECTIVE: To evaluate the effects of preoperative electrical stimulation on cutaneous wound healing in rats. METHODS: Forty rats were divided into two groups of 20 animals each. In the control group, an incision was made on back of the animals. In the stimulation group, a preoperative electrical stimulation was applied using a rectangular pulse current at a frequency of 7.7Hz, and intensity of 8mA, for 30 minutes, with the positive electrode placed on the back of the animal, and the negative electrode placed on the abdominal wall. Following, an incision was made on their back. Biopsy on the postoperative days 7 and 14, and histological analysis was performed. RESULTS: The stimulated group, at day 7, showed a greater number of newly formed vessels and fibroblasts, and a statistical difference with lower density of collagen type III, bud no statistical difference were observed for mast cells and fibers of collagen type I. CONCLUSION: Preoperative electrical stimulation with positive polarity increased the amount of fibroblasts and blood vessels and decreased the density of collagen type III in the scar at the postoperative day 7.